Acute liver failure: a message found under the skin. Issue 954 (5th April 2005) - Meier, M; Woywodt, A; Hoeper, M M; Schneider, A; Manns, M P; Strassburg, C P
Abstract : Acute liver failure is a rare syndrome with rapid progression and high mortality. It is characterised by the onset of coma and coagulopathy usually within six weeks but can occur up to six months after the onset of illness. Viral hepatitis, idiosyncratic drug induced liver injury, and acetaminophen ingestion are common causes. This report describes the case of a 35 year old man who presented with acute liver failure shortly after binge drinking. Repeated history taking disclosed a gluteal disulfiram implant that the patient had received to treat his alcohol dependence. The patient recovered with maximum supportive care after surgical removal but without liver transplantation. This case illustrates that only meticulous history taking will disclose the sometimes bewildering causes of acute liver failure.